Agricultural Communities’ Risk Assessment and the Effects of Climate Change: A Pathway Toward Green Productivity and Sustainable Development - Sohail, Muhammad Tayyab; Mustafa, Sohaib; Ali, Mazurina Mohd; Riaz, Sidra (Frontiers in Environmental Science, 2022)
This study was carried out to assess agricultural communities’ understanding of climate change, the adaptation measures being undertaken against climate change, and industrial wastewater irrigation. It was considered important to check agricultural communities’ understanding of climate change, as the majority of the study area belongs to the farming and industry sector. This study was based on primary data collected through a survey in the study area. The results of present study showed that agricultural communities with sufficient resources and assets consider themselves to be safer and more capable of coping with the negative effects of climate change. Agricultural communities used different techniques to deal with the impacts of climate change in present study area. This study produced findings about agricultural households’ adaptation tactics that are unique and will aid policymakers in assisting agricultural communities in their day-to-day activities and farming practices, as well as in the implementation of proper monitoring and public policies to ensure integration and sustainability. This research is based on the sustainable livelihoods approach (SLA), which investigates how livelihood assets support agricultural communities by combining household adoption/adaptation strategies and livelihood outcomes.